ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS PUBLIKASI ILMIAH GURU PNS DI SMP NEGERI 1 REMBANG DAN SMP NEGERI 3 PENGADEGAN KABUPATEN PURBALINGGA - Mugi Lestari; Muslih Faozanudin; Dyah Retna Puspita (The Indonesian Journal of Public Administration (IJPA), 2018)
Abstract: Generally, the productivity of scientific publication of civil servant teachers in Purbalingga District and especially in Kecamatan Rembang and Pengadegan is still low. Based on the results of previous research and expert opinion, the low productivity of teachers' scientific publications is caused by teacher motivation factors, teacher competence, teacher work load and social support. The purpose of this study to determine the magnitude of the influence of teacher motivation, teacher competence, teacher workload, and social support to the productivity of scientific publications of civil servant teachers in SMP Negeri 1 Rembang and SMP Negeri 3 Pengadegan Purbalingga District. This research method used quantitative research method of descriptive case study format. Research location in SMP Negeri 1 Rembang and SMP Negeri 3 Pengadegan Purbalingga District. The sampling technique used is saturated or census sampling where the research population is at once a sample. The results of this study indicate that there is a significant effect of teacher motivation factors, teacher competence, teacher workload and social support to the productivity of scientific publications of civil servant teachers in SMP Negeri 1 Rembang and SMP Negeri 3 Pengadegan Purbalingga District, either independently or simultaneously. The influence of teacher motivation is 48,6% with positive direction, teacher competence 33,9% with positive direction, teacher work load 28,4% with negative direction, and social support equal to 34,3% with positive direction. On the other hand, the influence of teacher motivation, teacher competence, teacher work load, and social support simultaneously to the productivity of scientific publication of civil servant teachers in SMP Negeri 1 Rembang and SMP Negeri 3 Pengadegan Purbalingga District is 53.1%. That is, as much as 46.9% productivity scientific publications teachers influenced by other factors outside this study.Keywords: Productivity of teachers' scientific publications, teacher motivation, teacher competence, teacher workload, social support. Abstrak: Secara umum, produktivitas publikasi ilmiah guru PNS di Kabupaten Purbalingga dan khususnya di Kecamatan Rembang dan Pengadegan masih rendah.  Berdasarkan hasil penelitian terdahulu dan pendapat para ahli, rendahnya produktivitas publikasi ilmiah guru PNS antara lain disebabkan oleh faktor motivasi guru, kompetensi guru, beban kerja guru dan dukungan sosial.  Tujuan penelitian ini untuk mengetahui besarnya pengaruh motivasi guru, kompetensi guru, beban kerja guru, dan dukungan sosial terhadap produktivitas publikasi ilmiah guru PNS di SMP Negeri 1 Rembang dan SMP Negeri 3 Pengadegan Kabupaten Purbalingga.  Metode penelitian ini menggunakan metode penelitian kuantitatif format deskriptif studi kasus. Lokasi penelitian di SMP Negeri 1 Rembang dan SMP Negeri 3 Pengadegan Kabupaten Purbalingga. Teknik sampling yang digunakan adalah sampling jenuh atau sensus dimana populasi penelitian sekaligus menjadi sampel.  Hasil penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan faktor motivasi guru, kompetensi guru, beban kerja guru dan dukungan sosial terhadap produktivitas publikasi ilmiah guru PNS di SMP Negeri 1 Rembang dan SMP Negeri 3 Pengadegan Kabupaten Purbalingga, baik secara mandiri maupun secara simultan/bersama-sama. Besarnya pengaruh motivasi guru secara mandiri sebesar 48,6% dengan arah positif, kompetensi guru sebesar 33,9% dengan arah positif, beban kerja guru sebesar 28,4% dengan arah negatif, dan dukungan sosial sebesar 34,3% dengan arah positif. Di sisi lain, besarnya pengaruh motivasi guru, kompetensi guru, beban kerja guru, dan dukungan sosial secara bersama-sama/simultan terhadap produktivitas publikasi ilmiah guru PNS di SMP Negeri 1 Rembang dan SMP Negeri 3 Pengadegan Kabupaten Purbalingga adalah 53,1%. Artinya, sebesar 46,9%  produktivitas publikasi ilmiah guru dipengaruhi oleh faktor lain di luar penelitian ini.Kata Kunci: Produktivitas publikasi ilmiah guru, motivasi guru, kompetensi guru, beban kerja guru, dukungan sosial.